Order fulfillment processing of a multi-zone warehouse - Anderson, Kurt A. (Kansas State University, 2014)
Inefficiencies in a warehouse that operates multiple zones can create bottlenecks in the order fulfillment process. This study’s focuses on the exploration of potential bottlenecks in an agricultural aftermarket company’s order fulfillment process and its multi-zone warehouse. Order fulfillment includes stages of order processing, SKU picking and staging from the conveyor zone and the “H” zone, and the final packaging and shipping of the order within the Truck Freight Department. A review of the company’s EOP program, and the effects of the program, provides additional insight into our understanding of bottlenecks within a dynamic the system. In doing so, the research will extend the existing knowledge on warehouse management with multiple zones. The conclusion of this paper offers solutions that will alleviate the bottlenecks and improve the overall efficiency of the order fulfillment process within a multi-zone warehouse.
Keywords: Multizone warehouse; Bottleneck; Fulfillment; Process; Economics, Commerce-Business (0505); Economics, Labor (0510); Labor Relations (0629); Management (0454)